Physical model tests and numerical simulation for assessing the stability of tunnels - Chen, Han-Mei (2014)
Nowadays, numerical modelling is increasingly used to assess the stability of tunnels and underground caverns. However, an analysis of the mechanical behaviour of existing brick-lined tunnels remains challenging due to the complex material components.